2021
DOI: 10.3390/jof7090680
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Substances Produced by Cercospora brachiata in Absence of Light and Evaluation of Antibacterial Activity

Abstract: Cercospora brachiata is a phytopathogenic fungus. To know more about the metabolites produced by this fungus, the objective of this work was to identify, isolate and characterize substances present in extracts of the growth broth and mycelium, using gas chromatography with mass spectrometry (GC-MS) and nuclear magnetic resonance (NMR). It was also objective to evaluate the antibacterial activity of the extracts. Among the compounds identified, fatty acids, esters, and steroids can be highlighted. The main comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…37.43 min) exhibited a molecular ion peak at m / z 399 [M + H] + and m / z 381 [M + H-H 2 O] + , corresponding to C 28 H 46 O after the loss of one water molecule. In comparison with the literature [ 21 ], compound 23 was identified as brassicasterol.…”
Section: Resultsmentioning
confidence: 85%
See 2 more Smart Citations
“…37.43 min) exhibited a molecular ion peak at m / z 399 [M + H] + and m / z 381 [M + H-H 2 O] + , corresponding to C 28 H 46 O after the loss of one water molecule. In comparison with the literature [ 21 ], compound 23 was identified as brassicasterol.…”
Section: Resultsmentioning
confidence: 85%
“…Compounds 1 and 2 were obtained as a white amorphous mixture and were identified as coprostanol and brassicasterol based on a comparison of their spectroscopic analysis data, including EI-MS ( Figure S1 ), GC-MS ( Figures S2–S4 ), the ratio of coprostanol to brassicasterol (88.5% to 11.5%), 1 H-NMR, and 13 C-NMR ( Table S1 ), with the reported literature data [ 20 , 21 , 22 ].…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…The mechanism of steroid antibacterial activity through interactions with lipid membranes results in damage to liposomes, thereby inhibiting the entry of nutrients into bacterial cells (Nadaraia et al, 2019;Felisbino et al, 2021;Sharaf et al, 2022). Similarly, tannin compounds inhibit bacterial growth through interactions with cell membranes, causing changes in the structure of cell membranes and damaging membrane function in bacteria (Carvalho et al, 2018;Maisetta et al, 2019;Olchowik-Grabarek et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, Cercospora is considered an important control subject. In contrast, some Cercospora species have been found to produce secondary metabolites with antibacterial and antifungal activities (Felisbino et al 2021;Mookherjee et al 2020). We previously reported that Cercospora sp.…”
Section: Introductionmentioning
confidence: 99%